Gomella Neonatología pediátricos Tratamiento, procedimientos, problemas durante la guardia, enfermedades y fármacos - Gomella, Tricia Lacy; Eyal, Fabien G.; Bany-Mohammed, Fayez (McGraw-Hill's AccessMedicina., 2020)
In this eighth edition, the table of contents has been formatted to make it easier for the user and we hope it will be more logical. Section I includes essential prenatal and postnatal topics such as "Fetal Assessment," "Obstetric and Newborn Anesthesia," "Newborn Resuscitation," and "Newborn Transportation." Section II covers the basic assessment and treatment of a newborn, with a new chapter entitled "The Golden Hour." Section III includes advanced treatment topics, such as the evolving areas of complementary and integrative treatments and two new chapters: "Genetic and Genomic Testing in the Neonatal Period" and "Neonatal Palliative Care." Section IV includes all the basic and advanced clinical procedures often performed in neonatology.chapter 44. We also include point-of-care ultrasound information in the relevant procedures. One of the most popular sections of the book, "Problems While On Call," now includes a total of 35 frequent neonatal problems with the addition of a new problem: "Abdominal Bloating." Section VI, "Diseases and Disorders," covers all common and a few not-so-frequent, but clinically important diseases of the newborn. We added a new subsection of "Infectious Diseases" to cover the growing literature on infectious diseases that can occur in the newborn. Two new chapters were added in this section dealing with dengue infection and the Zika virus. The section on neonatal pharmacology includes significant updates to drugs often used in newborns. As there are relatively few drugs formally approved for use in newborns, the drug information was carefully curated by our outstanding group of neonatal pharmacologists. We believe it is the most complete list of drugs found in a manual like ours. The chapter "Effects of Drugs and Substances on Newborn Breastfeeding" was revised to include the most common medications that a breastfeeding mother can use. The appendices include other useful tables and reference information. A distinctive feature of our book has been to point out areas that are "controversial" and this edition continues that tradition.